Green concrete or red herring? – future of alkali-activated materials. (November 2014) - Provis, J. L.
<x content-type="archive" xml:space="preserve">Abstract</x> Alkali-activated binders, including geopolymers, are widely considered to provide a pathway to the largescale production of 'green concretes', with commercialisation proceeding internationally, and scientific understanding developing at a rapid pace. In assessing any claims regarding the environmental performance of alkali-activated concretes, analysis of appropriate formulation and processing conditions as a function of geographic and raw materials supply parameters must be undertaken. Prediction of durability is also essential, and there remains much to be done in validation of durability test methods for these materials. Another key challenge in the use of any novel binder is compliance with regulatory standards. Updated standards in some jurisdictions show increasing acceptance of alkali activation technology in principle and in practice, showing that the need for sustainable binders can drive regulatory developments in this area and thus enable the uptake and utilisation of these materials. The advancement of scientific knowledge has proven essential in this process.